2017
DOI: 10.1002/pon.4344
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of attitudes toward length and quality of life between community‐dwelling older adults and patients with advanced cancer

Abstract: Findings indicate that attitudes towards length and quality of life differ by life stage. This has implications for end-of-life care decisions made by CDOAs, such as purchasing health or disability insurance and signing advance directives or care plans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 33 publications
(45 reference statements)
0
10
0
Order By: Relevance
“…A community survey of elderly people in the United States demonstrated that those with poorer functional status were more likely to have engaged in ACP, whereas a study in Singapore demonstrated that most adults aged over 50 years chose quality of life over length of life when compared with advanced cancer patients. (15,16) Such inclination increased with age. While relying solely on a modified Barthel Index < 80 to stratify patients would be an oversimplification, our study results show that stratification by functional status could indeed be considered and utilised as part of a collective strategy to help more patients achieve successful completion of ACP discussion.…”
Section: Discussionmentioning
confidence: 92%
“…A community survey of elderly people in the United States demonstrated that those with poorer functional status were more likely to have engaged in ACP, whereas a study in Singapore demonstrated that most adults aged over 50 years chose quality of life over length of life when compared with advanced cancer patients. (15,16) Such inclination increased with age. While relying solely on a modified Barthel Index < 80 to stratify patients would be an oversimplification, our study results show that stratification by functional status could indeed be considered and utilised as part of a collective strategy to help more patients achieve successful completion of ACP discussion.…”
Section: Discussionmentioning
confidence: 92%
“…In advanced cancer, where survival is commonly <1 year [1,2] and symptoms and side effects are prevalent and often debilitating [3,4], the fundamental challenge is to provide care to extend survival while simultaneously supporting quality of life [5][6][7][8][9]. Specialty palliative care programs are comprised of multidisciplinary teams of clinicians who meet with patients to support their quality of life, physically and psychologically, using specialized knowledge and skills to relieve the symptoms, side effects, and stress of serious illnesses [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The reference point for an advanced cancer patient with a short life expectancy will be closer to death compared to an older adult with many years of expected survival. Thus, ill patients would prefer prolonging their life over quality of life, as was found in the results [ 33 , 34 , 36 ]. Likewise, sick patients rated a mild and a severe disease situation very differently, but healthy patients rated the two scenarios as much more similar [ 35 ].…”
Section: Resultsmentioning
confidence: 70%
“…Another focus of PT study has been life attitudes in healthy and sick patients and reference point [ 33 , 34 , 35 , 36 , 37 ]. Current health status determines one’s reference point.…”
Section: Resultsmentioning
confidence: 99%